DEVELOPMENT OF E-JOBSHEET FOR REFRIGERATION INSTALLATION BASED ON SKKNI - Huda, Ahmad Khoirul; Setiodi, Wempi; Koswara, Anjar (Universitas Pendidikan Indonesia, 2024)
The purpose of this research is to create an SKKNI-based e-jobsheet in the subject of refrigeration installation systems that are feasible to use based on the assessment of media experts, material experts and measure student learning outcomes in the cognitive, psychomotor and affective domains and determine user response. The research method used is RnD by following the ADDIE model. The research sample taken was 31 students of class XI TPTUP. The instruments used in this study were expert validation sheets, pretest and posttest sheets, psychomotor and affective observation sheets, and user response questionnaires. The results of the feasibility assessment conducted showed that the e-jobsheet developed was categorized as